2023
DOI: 10.3892/ol.2023.13969
|View full text |Cite
|
Sign up to set email alerts
|

SLC17A9 expression levels in a pan‑cancer panel and validation of the role of SLC17A9 as a novel prognostic biomarker for osteosarcoma

Abstract: Previous studies have demonstrated the involvement of the solute carrier family 17 member 9 ( SLC17A9 ) in certain types of cancer; however, the precise role of SLC17A9 is not well defined. In the present study, a comprehensive analysis was performed to determine the involvement of SLC17A9 in a pan-cancer panel. First, data on SLC17A9 expression levels from publicly available databases were obtained to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Li and colleagues revealed that SLC17A9 promoted proliferation and invasion of clear renal cell carcinoma through PTHLH [ 36 ]. A recent study identified that SLC17A9 may serve as a novel prognostic biomarker for osteosarcoma and SLC17A9 expression was associated with stemness in osteosarcoma [ 37 ]. These findings inferred that SLC17A9 may act as a potential oncogene and an independent risk factor for overall survival of patients with various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Li and colleagues revealed that SLC17A9 promoted proliferation and invasion of clear renal cell carcinoma through PTHLH [ 36 ]. A recent study identified that SLC17A9 may serve as a novel prognostic biomarker for osteosarcoma and SLC17A9 expression was associated with stemness in osteosarcoma [ 37 ]. These findings inferred that SLC17A9 may act as a potential oncogene and an independent risk factor for overall survival of patients with various tumors.…”
Section: Discussionmentioning
confidence: 99%